SYSTEMATIC REVIEW ON EPIDEMIOLOGICAL STUDIES OF SCHISTOSOMIASIS IN SOKOTO STATE, NIGERIA (Journal of Biomedical Investigation, 2023)
Background of the study: Schistosomiasis has been as one of the dangerous neglected tropical diseases that cause huge socioeconomic health problems in many parts of Nigeria including Sokoto State. However, there is a dearth of information on the disease distribution, intensity and risk factors associated with the illness in the state.Aim of the Study: The present study was conducted to systematically review the prevalence, intensity and risk factors causing schistosomiasis infection in Sokoto state, Nigeria.Methodology: Information from more than five hundred (500) research articles at ResearchGate, ScienceDirect, PubMed, Google Scholar and World Health Organization (WHO) were gathered. However, only manuscripts that were found with relevant information needed for the sake of the present research were highly considered, articles that contained information on the prevalence, intensity, or risk factors associated with the schistosomiasis were given much emphasis, only articles in which at least their abstract was written in English language were considered.Results: Results from the available article showed that; the overall schistosomiasis infection rate across the state ranged from 2.9% to 61.8, and the overall intensity of the disease in the state was between 499.0 to 1.75. Identified risk factors in the State were: occupation, education, age group, personal habits socioeconomic status, personal hygiene and residence location.Conclusion: It was concluded that there is a high prevalence and intensity of schistosomiasis in Sokoto state, Nigeria as a result of many risk factors such as environmental, socioeconomic and demographic.Recommendation: It was recommended that further research should focus on investigating the antigenic factors responsible for the persistence of the parasite in the state to allow for best preventive and control measures.
Keywords: distribution; intensity; factors; schistosomiasis; Sokoto state